Prototype Pembangkit Listrik Tenaga Pikohidro dengan Memanfaatkan Instalasi Air Bersih - Prian Gagani Chamdareno; Deni Almanda; Hendra Gunawan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2019)
Electricity today is a primary need for humans. But the use of energy currently used comes from fossil energy, which is not renewable and will be depleted as time and technology evolve. Therefore, there is a need for renewable energy to take advantage of the energy around us. The use of alternative energy does not have to be large scale. This study has been designed to model the Pico hydro Power Generator using clean water installations. In this model, the water debit and the water flow velocity are calculated based on the change in the opening of the faucet. The highest measurement results were obtained when the open position was fully open, with a water flow speed of 0.0049 m / s and a voltage of 12.2 volts with no load conditions. Then a change in flow velocity and voltage after being provided with a 20 watt led light load of 0.0054 m / s with a voltage of 8.59 Volts and a current of 0.14 A.